1968
DOI: 10.5453/jhps.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 90Sr and 137Cs administered continuously and through Generations upon Mice

Abstract: and Sakiko IKEGUCHI Mice of NA-2 strain were administered continuously and through generations with 90Sr and 137Cs contained in drinking water. Concentration of the isotopes was divided into three levels; Group I: (90Sr and Group IV (Control) was fed with noncontaminated water. Abnormality of growth, life-span and reproduction in these groups were summed up till 10th generation. Group I showed shortening of lifespan and lost reproductive function already in 2nd generation. Group II showed injury of growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Experimental data on combined internal contamination plus external radiation exposures are very sparse, and are mainly limited to very early studies with a combination of 137Cs and 90Sr, but without any comparison with single radionuclide exposure (Nishio, 1968(Nishio, , 1969(Nishio, , 1971Nishio et al, 1968). It is thus difficult to compare our study of combined exposures with work from others, even with the study by Calvi et al (Calvi et al, 2019).…”
Section: Eimentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental data on combined internal contamination plus external radiation exposures are very sparse, and are mainly limited to very early studies with a combination of 137Cs and 90Sr, but without any comparison with single radionuclide exposure (Nishio, 1968(Nishio, , 1969(Nishio, , 1971Nishio et al, 1968). It is thus difficult to compare our study of combined exposures with work from others, even with the study by Calvi et al (Calvi et al, 2019).…”
Section: Eimentioning
confidence: 99%
“…The studies demonstrated a reduced life expectancy and a reduction of reproductive efficiency. However, in these studies there was no comparison between exposure with a single radionuclide and the mixture of the two radionuclides (Nishio et al 1968, Nishio 1968, 1969, 1971. This absence of study on the effect of combined exposure is probably linked to the hypothesis of additivity of health effects, as the absorbed dose is considered as additive, too.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Les recherches sur les effets biologiques de co-contaminations de radionucléides restent très limitées. Pour l'essentiel, il existe une série de travaux réalisées durant les années 1960 par une équipe japonaise sur 20 générations de souris contaminées via l'eau de boisson (Nishio, 1968 ;Nishio et al, 1968 ;Nishio, 1969 ;Nishio, 1971 90 Sr a été calqué sur ce qui a été retrouvé dans l'environnement à la suite des essais nucléaires aériens des années 1960 dans les îles du Pacifique. Il a été montré une altération de la durée de vie dans tous les groupes, avec un déficit de reproduction dans le premier groupe tel que l'expérience n'a pu être menée que jusqu'à la 8 e génération (Nishio, 1969).…”
Section: éTudes De Mélanges De Radionucléides Et De Polluants Chimiquesunclassified